Exploring the characteristics, acuity and management of adult ED patients at night-time. Issue 9 (30th July 2019) - Simpson, Rebecca; Croft, Susan; O'Keeffe, Colin; Jacques, Richard; Stone, Tony; Ahmed, Nisar; Mason, Suzanne M
Abstract : Objectives: ED care is required for acutely unwell and injured patients 24 hours a day, 7 days a week. The aim of this study was to compare characteristics and activity of type 1 ED attendances according to whether their time of arrival was during the day (08:00–18:00) or at night (18:00–08:00). Methods: Hospital Episode Statistics (HES) data from NHS Digital for all A&E and admitted patient care activity provided by all acute (not mental health or primary care) NHS hospital trusts in Yorkshire and Humber (1 April 2011 to 31 March 2014) for adult patients were analysed. Adjusted linear and logistic regression was used to model the data. Results: Adjusted regression analysis results show that patients who attended ED at night waited an extra 18.76 (95% CI 18.62 to 18.89) min to be seen by a clinician. They also spent an additional 13.64 (95% CI 13.47 to 13.81) min total in ED. Patients who attended at night were OR 2.20 (95% CI 2.17 to 2.23) times more likely to leave without being seen. They were also OR 1.26 (95% CI 1.25 to 1.27) times more likely to re-attend the ED and were OR 1.20 (95% CI 1.19 to 1.21) times more likely to present with non-urgent conditions. Overnight patients were more likely to be admitted to hospital, OR 1.09 (95% CI 1.09 to 1.10) times, however, those admitted were more likely to have a short-stay admission. Conclusion: There is an 'overnight effect' of patients attending EDs. Patients wait longer, leave without being seen, attend with non-urgent problems and are more likely to be admitted for a short stay. Further work is required to identify the potential underlying causes of these differences.